Impact of combined modality treatment with radiotherapy and S-1 on T2N0 laryngeal cancer: Possible improvement in survival through the prevention of second primary cancer and distant metastasis. (August 2017) - Kitani, Yosuke; Kubota, Akira; Furukawa, Madoka; Hori, Yukiko; Nakayama, Yuko; Nonaka, Tetsuo; Mizoguchi, Nobutaka; Kitani, Yuka; Hatakeyama, Hiromitsu; Oridate, Nobuhiko
Highlights: Impact of combined modality treatment with radiotherapy (RT) and S-1 on T2N0 laryngeal cancer was evaluated. The lower incidence of second primary cancer and distant metastasis was observed in patients treated with combined modality treatment with RT and S-1. Abstract: Background: In patients with head and neck cancer, the management of second primary cancer (SPC) is particularly important for improving survival because of its high incidence and associated mortality. We evaluated the impact of combination chemotherapy on survival and SPC. Method: We retrospectively analyzed data from 49 patients treated with definitive radiation therapy (RT) for T2N0M0 laryngeal squamous cell carcinoma between 2003 and 2011. Among them, 22 patients received combined modality treatment with radiotherapy and S-1 (RT + CT group). Results: The median follow-up period was 71 months (32–111 months). A significant difference in overall survival (OS, P < 0.01) was observed between the RT + CT group (n = 22) and the RT alone group (n = 27) though no significant differences were observed in local control and disease specific survival. Univariate analyses showed that an older age ( P < 0.05) and a higher grade ( P < 0.05) were associated with OS. Multivariate analysis identified chemotherapy as the most significant predictor of survival (OR, 0.056; 95% CI, 0.008–0.353, P < 0.01). A significantly lower incidence of distant metastasis (DM) + SPC (5-year incidence: 5% vs. 19%, P < 0.05) and fewer deaths from these causes (1 vs. 8: P < 0.05) were observed in the RT + CT group. Multivariate analysis showed that chemotherapy was the most significant factor for the incidence of DM + SPC (OR, 0.074; 95% CI, 0.0065–0.84; P < 0.05). Conclusion: The findings of this study suggest the possibility that combined modality treatment with radiotherapy and S-1 improve survival by preventing distant metastasis and second primary cancer.